Motion based video super resolution using edge directed interpolation and complex wavelet transform - Izadpanahi, S.; Demirel, H. (Elsevier Science Bv, 2013)
This paper proposes a novel super resolution technique using dual tree complex wavelet transform (DT-CWT) and new edge directional interpolation (NEDI) based on localizing motion blocks in consecutive frames. A super resolution process is applied on the extracted motion blocks and the static region of the frame to generate the low frequency subbands of DT-CWT. DT-CWT decomposition followed by NEDI generates the high frequency subbands in order to obtain the components required for inverse DT-CWT (IDT-CWT). Finally, the super resolved output frame is generated by composing the obtained high and low frequency subbands using IDT-CWT. Experimental results based on PSNR measures illustrate the advantage of proposed technique over the state of the art video resolution enhancement methods. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Wavelet transform; Interpolation; Super resolution